Precious House of Pancakes Cafe / Nommy Paulus... [et al.] - Abdul Rahman, Nurul Aqilah; Lairis, Leduinah; Jaiman, Siti Noorafilah; Saidin, Haslina; Paulus, Nommy (2014)
PHOP Sdn. Bhd. is a new company that operated in Malaysia. It is the first company that being managed by bumiputera. The name of this company is come out form the imagination by the partnerships members. It shows that how we positioning our products in customers' mind until they can remembering our company's name, simple and easy to pronounce. As for the business, we are providing a special, delicious pancake for the Malaysian. As we go through with the changes of environment, people nowadays don't put on simple food on their own daily meals. So, our surveying we conclude that we are going to provide the Malaysia with the simple and special pancakes, that are will in high product's quality. We are starting the business with the total capital of RM250, 000 and all of the partners are contributing RM10,000. We have five workers that are general manager, administration manager, marketing manager, operational manager and financial manager. Our market target of customers' characterististic is come from all income level, and for all of the customers' level of ages. Even children also can effort to buy our products. Business plan is necessary to all entrepreneurs. It is prepared to a group of people which are owners itself, bankers, suppliers, customers and employees. This plan include in Business Plan chapter which is consists of marketing, operation, organization and financial plan. We are believe that we will be able to achieve our business goal with our business financial position statement. We will get our return modal within short time and our current ratio will cover our liabilities and put our business in comfort stage with the highest.